INTEGRATION OF DEVELOPMENT PROGRAMS BASED ON COLLABORATIVE GOVERNANCE ON REGIONAL POLICIES AND VILLAGE - Itok Wicaksono (POLITICO, 2021)
The disharmony of the relationship between the local government and the village government has been felt since the enactment of Law no. 6 of 2014. The excessive and often misunderstood spirit of village autonomy for most village governments seems to have resulted in a disharmony relationship with the local government above it. Therefore, it is necessary to integrate authority in order to produce strategic policy outputs that are needed to advance and improve people's welfare. The integration of the implementation of village development between local and village governments needs to be addressed. Integration can be built in two ways, namely: communication and coordination. There are 3 ways of integration that must be done by local governments, among others; integrated in the field of authority, integrated in the financial sector, and integrated in the field of public services-SDA. To realize the integration of the authority of the local government and village government, Collaborative governance is an alternative as an interactive process that involves a group of people autonomously who utilizes shared rules with norms and organizational structures to solve problems, reach agreements to take joint actions, and share resources such as information, funds, or staff.